Spring and autumn movements of an Arctic bird in relation to temperature and primary production. (1st October 2021) - Doyle, Susan; Cabot, David; Griffin, Larry; Kane, Adam; Colhoun, Kendrew; Bearhop, Stuart; McMahon, Barry J.
Abstract : It is increasingly important to understand animal migratory movements because climate disruption is shifting plant and animal phenology at different rates across the world. We applied a Markov state‐switching model to telemetry data of a long‐distance migrant, the barnacle goose, to detect migratory movement and relate it to three proximate environmental factors: photoperiod, daily mean temperature and forage plant phenology. Spring migratory movements towards the breeding grounds were most closely related to forage plant phenology (measured by accumulated growing degree days, GDDs); high GDDs values were associated with a greater probability of transiting to a more northerly site, suggesting that spring migration is closely aligned with primary productivity. Autumn migration from the breeding grounds was most closely related to temperature; higher temperature values were associated with a greater probability of remaining settled at the current site, suggesting that autumn migration is closely aligned with atmospheric conditions. Understanding the relative influence of different environmental factors on migratory patterns may in turn provide us with insight into how continued climate disruption could influence northern migratory systems.